STRATEGIC PARTNERSHIPS WITH INTERNATIONAL INSTITUTIONS AS A FACTOR IN IMPROVING THE EFFECTIVENESS OF LAW ENFORCEMENT IN UKRAINE - Kozhyna, Alla; Petkun, Svitlana; Larina Natalіia (Public Management and Policy, 2026)
This article provides a comprehensive theoretical justification of the role of strategic partnerships with international institutions as a fundamental factor in the modernization of public administration within Ukraine’s law enforcement sector. It is demonstrated that, against the backdrop of martial law and the intensification of negotiations on accession to the European Union, law enforcement activities are transforming into a complex networked ecosystem, where the effectiveness of national actors depends directly on the quality of their integration into international security networks. Particular attention is paid to analyzing the dynamics of EU law throughout 2024, specifically the Directives on the criminalization of sanctions regime violations and the harmonization of asset confiscation rules. The feasibility of implementing an analytics-driven model of law enforcement and the use of a methodology for strategic forecasting of transnational threats is substantiated. The concept of ‘management resonance’ is explored as a necessary mechanism for synchronizing the efforts of administratively independent agencies with international security standards. The paper details four conceptual elements of a strategic partnership: regulatory convergence of domestic legislation, institutional transparency through international standards for personnel selection, technological compatibility of digital security systems, and the alignment of government narratives. It is demonstrated that strategic communications and professional communication management are tools for building the state’s ‘communicative capital’, which enhances public trust and legitimizes law enforcement reforms. The conclusions emphasize that strategic partnership ensures the transition to a people-centred doctrine of protecting rights and freedoms, making the European integration progress of Ukraine’s law enforcement system an irreversible process of institutional excellence.